2004
DOI: 10.1158/1078-0432.ccr-1041-03
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization by Pan ErbB Inhibitor CI-1033 in Vitro and in Vivo

Abstract: Purpose: Overexpression of the ErbB family of receptor tyrosine kinases has been associated with uncontrolled growth of many tumor types and, therefore, presents a promising molecular target for cancer therapy. CI-1033 is a small molecule tyrosine kinase inhibitor that differs from other 4-anilinoquinazolines by being a pan ErbB (instead of epidermal growth factor receptor-specific) irreversible (instead of reversible) inhibitor. Therefore, we investigated the antitumor effect of CI-1033 alone and in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 29 publications
(30 reference statements)
7
48
0
2
Order By: Relevance
“…Potential cancer therapies must not only inhibit cell growth in vitro but also must be able to inhibit tumor growth in the complex in vivo environment. Several researchers have reported that CI-1033 treatment of athymic nude mice bearing xenografts of epidermoid carcinoma, non-small cell lung carcinoma, glioblastoma, and breast and colon cancer results in highly significant suppression of tumor growth (26,27,50). Our study showed that treatment with CI-1033 completely prevents the growth of esophageal squamous cell carcinoma xenografts.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Potential cancer therapies must not only inhibit cell growth in vitro but also must be able to inhibit tumor growth in the complex in vivo environment. Several researchers have reported that CI-1033 treatment of athymic nude mice bearing xenografts of epidermoid carcinoma, non-small cell lung carcinoma, glioblastoma, and breast and colon cancer results in highly significant suppression of tumor growth (26,27,50). Our study showed that treatment with CI-1033 completely prevents the growth of esophageal squamous cell carcinoma xenografts.…”
Section: Discussionsupporting
confidence: 63%
“…Since cisplatin is one of the most active chemotherapeutic agents for the treatment of esophageal cancer, enhanced antitumor activity by the combination of this drug and CI-1033 may be observed in clinical trials. In addition, some studies indicate that CI-1033 has synergistic effects when combined with ionizing radiation in breast, colon cancer and bile duct carcinoma (27,28,52). If CI-1033 is used in esophageal cancer therapy in the future, the concurrent use of other treatment strategies, such as chemoradiotherapy, should be included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Consistent with our data, high expression of ErbB1 and/or ErbB2 in both cell lines was reported in previous studies (16)(17)(18). As expected based on the ErbB protein expression data, the proliferation of both cells was stimulated by heregulin in a concentration-dependent manner.…”
Section: Mitogenic Effect Of Heregulin In Erbb-expressing Colon Cancesupporting
confidence: 94%
“…After cells were harvested in TRIzol (Invitrogen Co., Carlsbad, CA, USA), RNA was extracted and reverse transcribed into cDNA as described previously (Nyati et al, 2004). Quantitative PCR (QPCR) was then performed using SYBR Green dye on an Applied Biosystems 7300 Real-time PCR system (Applied Biosystems, Foster City, CA, USA) as described previously (Tomlins et al, 2005).…”
Section: Rna Isolation and Quantitative Pcrmentioning
confidence: 99%